Electronic publishing and open acces to information: the Nigerian situation - Ikponmwosa, Obaseki Tony; Schorlastica, Nkwoma; Ngozi, Ukachi B. (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2014)
Publishing has transited from traditional to Electronic format making information resources available to users without much subscription. E-publishing is engendered by the introduction of information and communication technology (ICT), this development has brought about increase in the number of scholarly communication in circulation. The awareness and rate of e-publishing differs among faculties, it based on this that this study was carried out to survey the situation of e-publishing and open access of librarians in three federal universities in Southern Nigeria, five research questions were formulated to guide the study. The methodology adopted is descriptive survey, questionnaire was given to a total population of 64 librarians consisting of librarians from the institutions understudy, the data collected from the study shows that though librarians are aware of e-publishing but they have not being publishing as should have been expected in University of Nigeria Nsukka (UNN) out of the 95% that aware of electronic publishing only 30% have published there articles electronically, in University of Lagos (UNILAG) 100% indicated that they have published electronically while in University of Benin (UNIBEN) 45.4% percent indicated yes while 54.5% said they have not published their articles electronically. On availability of open access it was discovered that they have access as a total of 84% from UNN responded Yes, UNILAG 100% said Yes while in UNIBEN 90.9%. The following problems based on their scoring militating against e-publishing and open access in Nigeria. Inadequate power supply; inadequate computer terminals; inadequate funding for subscription payment. Keywords: Electronic Publishing. Open Access. Library. Research.Link para o texto completo (PDF)http://www2.marilia.unesp.br/revistas/index.php/bjis/article/view/1776/2442